Wideband characterization of ultrasound transducers and materials using time delay spectrometry - LEWIN, P. A.; SCHAFER, M. A. (Archives of Acoustics, 1992)
This paper describes a procedure based on a swept frequency technique which provides wideband characterization of ultrasound transducers and materials. The procedure utilizes the Time Delay Spectrometry (TDS) principle and features significantly improved signal to noise ratio when compared to other conventional swept frequency systems. The experimental data illustrate the main advantages of the technique. In particular, they demonstrate the use of TDS to determine key parameters of acoustic transducers including transmitting and receiving frequency response, directivity patterns, and effective aperture. In addition, measurements of material acoustic attenuation are shown as a virtually continuous function of frequency.